Value-Added Analysis Of Cashew Processing Business In Watulea Village, Gu Sub-District Central Buton District - Apriani, Apriani; Bafadal, Azhar; Zani, Munirwan (International journal of technology and education research, 2024)
This study aims to evaluate the value added generated from the processing of cashew nuts in Watulea Village, Gu District, Central Buton Regency, as well as to analyze the costs, revenue, and profits associated with the processing. This research is a case study. Respondents in this study are business owners, employees, and consumers of the cashew nut processing business. Data collection techniques were done through observation, interviews, and documentation. There are two types of data used in this study: qualitative descriptive and quantitative descriptive. The data analysis methods used are qualitative and quantitative methods. The qualitative method is conducted through descriptive analysis to understand the processing of fried cashew nuts. The quantitative method is conducted through financial analysis to determine the level of costs and value added in the processing of fried cashew nuts. Based on the research, it can be concluded that the Household Industry in the cashew nut business in Watulea Village, Gu District, Central Buton Regency, generates an average daily revenue of Rp 3,900,000 with a total daily cost of Rp 2,975,967, resulting in an average daily profit of Rp 924,033. Furthermore, the value added generated from the Household Industry Production of cashew nuts is Rp 4,750 with a ratio of 25.333%, indicating a high value added from the processing of cashew nuts